NUMERICAL STUDY ON BEHAVIOUR OF COLD-FORMED STEEL UNLIPPED CHANNEL SUBJECT TO AXIAL COMPRESSION - Hidayat Mughnie; Budiman Budiman; Rachmad Irwanto; Muhammad Taufiq Al Hafidz (University Of Muhammadiyah Jakarta, 2022)
Innovation in obtaining construction materials that are efficient and applicable to various conditions is a challenge for researchers. Cold-formed steel is a material breakthrough in construction that has advantages over hot-rolled steel. Many studies have been carried out on Cold-formedsteel subjected to various loadings to examine the behavior and capacities of the sections. This study aims to investigate the behavior and section capacity of cold-formed steel unlipped channels due to axial compression loads. This research begins with conducting a literature study, then carrying out numerical analysis using the finite element method in ABAQUS, numerical test, and calculation of section capacity based on existing research in the literature. The calculation of section capacity is carried out based on SNI 7971-2013 or AS/NZS 4600:2005. The results of the numerical analysis can be seen from the behavior and capacities of the sections of the unlipped channel, the section capacity from the numerical test will be compared with the section capacity obtained from the calculation based on SNI 7971-2013 or AS/NZS 4600.